The story of "me" : contemporary American autofiction - Worthington, Marjorie (Frontiers of narrative., 2018)
"The Story of "Me" shows that the burgeoning of autofiction serves as a barometer of American literature from modernist authorial effacement to postmodern literary self-consciousness"--